PELAYANAN AKTA KELAHIRAN OLEH DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BATU - Selpianti . (Universitas Tribhuwana Tunggadewi, 2016)
Abstract: One of the efforts undertaken by the government in improving the quality of services can be seen through the ministry of making a birth certificate. A birth certificate is very important because it involves the identity and citizenship, as stated in Law No. 23 of 2002 on the Protection of the Child states that